The Influence Of Human Resources In Employment Recruitment Process At Bri Branch Office Bengkulu For The 2020-2022 - Putri, Lydia Gustina; Melinda, Tri Febrina (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Recruitment is the process of finding and selecting the right candidate to fill a certain position in an organization or company. This is done to ensure that the organization has a qualified workforce that suits the needs of the company, so that it can contribute to achieving the set business goals. The recruitment process includes searching for candidates, selecting and placing employees according to predetermined qualifications, competencies and criteria. In addition, recruitment is also carried out to obtain variety in terms of background and work experience of candidates, so that the organization can have diverse employees and can provide added value to the company. Employees are an important resource for the company, because they have the mind, talent, energy, desire, knowledge, feelings and creativity that are needed by the company to achieve the company's vision and mission (Mangkunegara, 2009). The success or failure of a company or organization and operational targets cannot be separated from the role of competent employees. The method used is a literature study with a descriptive exploratory approach.